2012
DOI: 10.1016/j.apmr.2012.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Central Hypersensitivity in Patients With Subacromial Impingement Syndrome

Abstract: Objective To investigate the presence of primary and secondary hyperalgesia among subjects with chronic subacromial impingement syndrome (SIS) compared to pain-free controls. Design Cross-sectional design. Setting Outpatient rehabilitation clinic, urban, academic medical center. Participants Volunteer sample of 62 subjects (31 with SIS, 31 controls). Interventions Not applicable. Main Outcome Measures Pressure-pain thresholds (PPTs) were measured at the middle deltoid of the affected/dominant arm (pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
83
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(86 citation statements)
references
References 25 publications
(34 reference statements)
1
83
1
1
Order By: Relevance
“…Some authors suggest changes in central (Hidalgo-Lozano et al, 2010;Paul et al, 2012) and peripheral (Alburquerque-Sendín et al, 2013) nervous systems in individuals with unilateral SAPS. These previous studies observed hyperalgesic responses to different stimuli i.e., pressure and thermal, at different anatomic regions in individuals with unilateral shoulder pain compared to matched healthy controls (Alburquerque-Sendín et al, 2013;Coronado et al, 2011Coronado et al, , 2014Hidalgo-Lozano et al, 2010;Paul et al, 2012;Sanchis et al, 2015). Our results do not support the presence of these hyperalgesic responses to mechanical stimuli in patients with clinical diagnosis of SAPS.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Some authors suggest changes in central (Hidalgo-Lozano et al, 2010;Paul et al, 2012) and peripheral (Alburquerque-Sendín et al, 2013) nervous systems in individuals with unilateral SAPS. These previous studies observed hyperalgesic responses to different stimuli i.e., pressure and thermal, at different anatomic regions in individuals with unilateral shoulder pain compared to matched healthy controls (Alburquerque-Sendín et al, 2013;Coronado et al, 2011Coronado et al, , 2014Hidalgo-Lozano et al, 2010;Paul et al, 2012;Sanchis et al, 2015). Our results do not support the presence of these hyperalgesic responses to mechanical stimuli in patients with clinical diagnosis of SAPS.…”
Section: Discussionmentioning
confidence: 98%
“…There is evidence suggesting the presence of unilateral regional shoulder mechanical hyperalgesia in these patients (Alburquerque-Sendín et al, 2013), whereas multiregional and bilateral shoulder pain hyperalgesia has been also documented (Hidalgo-Lozano et al, 2010;Paul et al, 2012). Both peripheral (Alburquerque-Sendín et al, 2013) and central (HidalgoLozano et al, 2010;Paul et al, 2012) sensitization mechanisms are suggested in playing a role in SAPS.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Patients with SIS have significantly lower pain pressure thresholds than do controls in both local and distal areas from their affected arm consistent with primary and secondary hyperalgesia, respectively. Data suggest the presence of central sensitization among subjects with chronic SIS [17]. Sleep disturbance which is very frequently seen in chronic pain patients can increase pain perception.…”
Section: Discussionmentioning
confidence: 91%